Winter Survival and Resource Use of Translocated Northern Bobwhite in the Mid-Atlantic United States - Kaili Stevens; Christopher K. Williams; Theron Terhune; Philip Coppola; John Parke; John Cecil (National Quail Symposium Proceedings, 2022)
Northern bobwhite (Colinus virginianus; hereafter, bobwhite) in the Mid-Atlantic United States have been experiencing precipitous population declines due to a combination of habitat deterioration, urban and suburban sprawl, change in forest management regimes, and farming practices. In recent years, restocking of bobwhite through translocation efforts has gained interest to rebuild local populations. However, empirical studies are warranted to understand the limitations of translocation as it relates to its potential use for long-term population recovery and persistence in this region. Further, few studies nation-wide have evaluated resource use and survival during the non-breeding season on translocated sites. As such, we translocated 360 bobwhites from source populations from southern latitudes during March–April 2015–2017 into 2 different landscape types similar to the source population vegetative communities (agricultural cropland dominated in Maryland, USA versus pine forest dominated in New Jersey, USA) and tested the effects of habitat fragmentation on survival and habitat use during the subsequent non-breeding season. We found habitat fragmentation negatively affecting survival and resource use among translocated bobwhite on fragmented cropland-dominated sites as compared to larger unfragmented forested sites. Survival was lower on cropland sites compared to forested sites such that bobwhite in cropland-dominated landscapes were >125 times less likely to survive the winter than those on forested sites. In our examination of resource use, bobwhite in structurally complex forested sites used cut pine, early-successional woody, early-successional herbaceous, and thinned pine more than what was available on the landscape. On the cropland sites bobwhite used food plots, early-successional woody, and mixed woods more than what was available on the landscape and only food plots at the home range scale. While larger unfragmented forested bobwhite habitat ultimately provided a more successful translocation landscape, birds still had large home ranges and relatively low survival. Therefore, proper pine management may be necessary to optimize habitat availability during the non-breeding season. Our findings provide rare information on demographic resiliency and resource use for translocated bobwhite during the non-breeding season. Further, this research provides valuable information to improve future translocation efforts in the Mid-Atlantic.
Keywords: Colinus virginianus; habitat use; pine forest; resource use; reintroduction; survival; translocation